Penyusunan Laman Menulis Berita untuk Kegiatan Ekstrakurikuler Jurnalistik SMA - Ardi Wina Saputra (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2019)
This research aims to create a writing website as a media to coach extracurricular activity in journalism, especially in news story writing. The research applied a Research and Development Model in which date were collected through questionnaries and interviews with experts in media, materials, teachers, and students of extracurricular activities in journalism.